2011
DOI: 10.1186/1471-2407-11-478
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic errors in hospitalised cancer patients: attributable damage and extra costs

Abstract: Background: In spite of increasing efforts to enhance patient safety, medication errors in hospitalised patients are still relatively common, but with potentially severe consequences. This study aimed to assess antineoplastic medication errors in both affected patients and intercepted cases in terms of frequency, severity for patients, and costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
140
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(155 citation statements)
references
References 30 publications
4
140
0
11
Order By: Relevance
“…Based on our previous results [21,23], selected events included recent, frequent and severe errors (i.e. errors that contributed to patient damage) or near-miss errors (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous results [21,23], selected events included recent, frequent and severe errors (i.e. errors that contributed to patient damage) or near-miss errors (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies of medication errors in cancer care report high rates of severe events [18,19,20]. In a previous study, we found that approximately 5% of anti-neoplastic prescriptions contained at least one medication error [21]. Moreover, errors involving anti-neoplastic agents are recognised as the second most common cause of death related to medication errors [22].…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous antineoplastic agents present additional safety challenges. [1][2][3][4] In addition to patient safety concerns, antineoplastic preparation and administration create significant staff risks. [5][6][7][8][9] The medication use system includes several stages that are vulnerable to opportunities for potentially harmful medication errors (MEs), such as incorrect drug, dose, concentration, or storage.…”
Section: Introductionmentioning
confidence: 99%
“…Eine Datenanalyse einer französischen Universitätsklinik zeigte, dass es bei insgesamt 6607 Verordnungen für stationäre Krebspatienten im Laufe eines Jahres in 341 Fällen (5,2%) zu mindestens einem Medikationsfehler gekommen war; insgesamt waren das 449 Fehler. Nur 436 davon wurden erkannt[2]. Eine weitere Analyse der erkannten Medikationsfehler durch unabhängige Ärzte ergab, dass es bei Nichterkennung in 2,6% der Fälle zu dauerhaften Schädigungen und in 1,8% zum Tod der Patienten gekommen wäre.…”
unclassified